Preventing Oxidative Stress in the Liver: An Opportunity for GLP-1 and/or PASK - Verónica Hurtado-Carneiro; Pilar Dongil; Ana Pérez-García; Elvira Álvarez; Carmen Sanz (MDPI AG, 2021)
The liver's high metabolic activity and detoxification functions generate reactive oxygen species, mainly through oxidative phosphorylation in the mitochondria of hepatocytes. In contrast, it also has a potent antioxidant mechanism for counterbalancing the oxidant's effect and relieving oxidative stress. PAS kinase (PASK) is a serine/threonine kinase containing an N-terminal Per-Arnt-Sim (PAS) domain, able to detect redox state. During fasting/feeding changes, PASK regulates the expression and activation of critical liver proteins involved in carbohydrate and lipid metabolism and mitochondrial biogenesis. Interestingly, the functional inactivation of PASK prevents the development of a high-fat diet (HFD)-induced obesity and diabetes. In addition, PASK deficiency alters the activity of other nutrient sensors, such as the AMP-activated protein kinase (AMPK) and the mammalian target of rapamycin (mTOR). In addition to the expression and subcellular localization of nicotinamide-dependent histone deacetylases (SIRTs). This review focuses on the relationship between oxidative stress, PASK, and other nutrient sensors, updating the limited knowledge on the role of PASK in the antioxidant response. We also comment on glucagon-like peptide 1 (GLP-1) and its collaboration with PASK in preventing the damage associated with hepatic oxidative stress. The current knowledge would suggest that PASK inhibition and/or exendin-4 treatment, especially under fasting conditions, could ameliorate disorders associated with excess oxidative stress.